ANALYSIS OF NORMATIVE LEGAL ASPECTS OF ROAD ACCESS CLOSURE BY GWK REGIONAL ADMINISTRATORS IN THE PERSPECTIVE OF LICENSING LAW IN INDONESIA - Aris Alfian; IM. Arjaya (Ikatan Dosen Menulis, 2025)
This normative juridical research examines the legal limits on the authority to close road access exercised by the manager of the Garuda Wisnu Kencana Cultural Park within the framework of Indonesian licensing law. The central inquiry is whether private entities holding Building Rights have the legitimate authority to restrict public highways unilaterally and how the licensing mechanism balances private development rights with community welfare obligations. Using the analysis of Law Number 38 of 2004 concerning Roads, Law Number 5 of 1960 concerning Agrarian Basic Principles, and Government Regulation Number 5 of 2021 concerning Risk-Based Licensing, this study analyzes primary legal materials complemented by academic literature. The investigation revealed that the GWK manager did not have absolute authority to close public roads, as the Right to Use of Buildings remained limited by the constitutional principles governing the social function of land, as outlined in Article 6 of the Agrarian Constitution and Article 33 of the 1945 Constitution. The licensing mechanism serves as an important administrative control instrument, ensuring that private activities comply with the principles of legality, proportionality, and accountability. However, there are systemic shortcomings in the implementation of supervision and integration of social impact assessments. The study concludes that comprehensive legal reforms are needed, including mandatory Social Impact Assessment procedures, enhanced oversight mechanisms, and more explicit statutory clarification of the relationship between private development rights and established patterns of public access. This study contributes to the science of Indonesian administrative law by demonstrating that effective licensing governance requires integrating legal control mechanisms with participatory community involvement to achieve equitable spatial development.